Estudo de interseções mínimas canalizadas com base em níveis de serviço - Douglas Wendel Consoli , Ozelame (2022)
Ribbed slabs have established themselves as an excellent solution for the construction of building floors, however most of the structural analyzes for this construction system are simplified and can provide results that are not always reliable regarding the behavior of the structure, this is because some of these simplifications disregard factors that influence in the final displacement of the ribbed slab. Although progress on the subject of structural analysis of ribbed slabs that consider methods close to reality, such as the finite element method, is significant, there are still factors that require elucidation. Therefore, this dissertation aims to analyze the best ways to model ribbed slabs, evaluating the influence of considering the massive region adjacent to the edge beam and the influence of the structure's geometry on the final displacement of the ribbed slab. Firstly, the research focuses on finite element calculation models for representing ribbed slabs, with the aim of observing the validation parameters of numerical analyzes determined in the reproduction of analytical, numerical and experimental studies. Subsequently, three finite element modelings are proposed, where the first modeling consists of considering the ribs modeled up to the middle surface of the edge beams, the second modeling considers the formation of a massive region adjacent to the edge beam modeled only by the layer of concrete and, finally, a modeling that considers the solid region adjacent to the edge beam modeled separately, in addition to modeling via grid analogy, with the objective of analyzing twenty-three slabs that had the width, height and spacing between axes of varied ribs in order to verify the influence of each variable and the difference in results between the modeling methods. The results obtained determine, firstly, the importance of the eccentricity between the axes of the rib and the concrete plate so that more realistic results can be achieved; second, that increasing the height and width of the ribs reduces the final displacement; third, that resorting to finite element modeling is a prominent solution for the analysis, given that factors such as the massive region adjacent to the edge beam, often neglected by other modeling, interfere with obtaining a realistic modeling. It is also noted that the grid analogy offers practicality and ease of analysis. Finally, it is understood that this study forges its contribution in the instance of different ways of numerical modeling for structural analysis of ribbed slabs through the finite element method, in addition to considering parametric analysis to evaluate the final displacement of the structure and the cost for different heights and widths of the ribs, and variation in the spacing between ribs.